Energy, Exergy, and Economic Analyses and Optimization of Solar Organic Rankine Cycle with Multi-objective Particle Swarm Algorithm - A. Beiranvand; M.A. Ehyaei; A. Ahmadi; Jose Luz Silvaria (Renewable energy research and applications (Online), 2021)
The high potential of solar energy in Iran, as well as the problem of air pollution, makes it increasingly inevitable that solar energy is used. In this study, the solar-powered Organic Rankine cycle (ORC) has been investigated. The solar-type collector is a flat plate collector. The energy, exergy, and economic analyses of the hybrid system with the MOPSO algorithm have been carried out for Tehran., the capital of Iran. The working fluid of the solar collector has assumed water and the working fluid of the ORC cycle is R123. The MATLAB software is used for simulation and to compute the R123 fluid properties, the Refprop software is used. The exergy investigation shows that the most exergy destruction is related to the evaporator. Two objective functions consist of exergy efficiency and the price of electricity are considered. The decision variables for this optimization are considered as; the number of solar collector panels, the pump, and turbine isentropic efficiencies, and the pressure of condenser and evaporator. The Pareto diagram shows that the exergy efficiency of the system can vary as 7.5 % to 10.5 %, as well as the price of produced electricity can vary from 0.2 to 0.26 to $/kWh.